Analisis gaya belajar siswa pada pebelajaran IPA kelas IV SD - Rahmah, Nur Lailatur (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research is motivated by the lack of innovative learning in learning and the lack of facilities and infrastructure in science learning. The researcher uses a qualitative descriptive method which aims to analyze and describe a condition of each data collected, in the form of observations about the problems that exist in the field. Data collection techniques in this study using observation and questionnaires. The data analysis technique in this study uses the analysis of the Miles and Huberman model. consists of several steps used, namely data reduction (data reduction), data display (data presentation) and verification (conclusions). Based on the results of the study, it canbe concluded that the learning style that stands out in the fourth grade of primary school of Sidoarjo is the visual learning style.